A Friendship Values of Anna in the Novel When Marnie Was There by Joan G Robinson - Pasha, Mutiara Andara; Sukmawaty, Fenty; Saprudin, Saprudin (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
The title of this research is the Friendship Values ​​of Anna in the Novel When Marnie Was There by Joan G Robinson. This study aims to find out how the two main characters, namely Anna and Marnie, live their friendship. This study uses descriptive qualitative methods to describe Anna and Marnie's friendship values, the approach used in this study is an objective approach. The results of this study show that the friendship of the two characters, namely Anna and Marnie, has friendship values ​​of self-disclosure, intimacy, self-esteem support, loyalty, prosaically behavior. Keyword: Main Character, Friendship, Friendship values